Risk Factors for Sexual Offending in Self-Referred Men With Pedophilic Disorder: A Swedish Case-Control Study - Wittström, Felix; Långström, Niklas; Landgren, Valdemar; Rahm, Christoffer (Frontiers in Psychology, 2020)
Background The risk of child sexual abuse among non-forensic, non-correctional patients with Pedophilic Disorder (PD) is largely unknown. Methods We recruited a consecutive sample of 55 help-seeking, non-correctional adult men diagnosed with DSM-5 PD at a university-affiliated sexual medicine outpatient unit in Sweden. PD participants were compared with 57 age-matched, non-clinical control men on four literature-based dynamic risk domains and self-rated child sexual abuse risk. Results PD participants scored higher than controls on all tested domains (0–3 points); expectedly so for pedophilic attraction (2.5 vs. 0.0, Cohen’s d = 2.40, 95% confidence interval (CI): [1.91–2.89]), but also for sexual preoccupation (1.6 vs. 1.0, d = 1.11, 95% CI: [0.71–1.51]), impaired self-regulation (1.4 vs. 1.0, d = 0.44, 95% CI: [0.06 to 0.81]), impaired cognitive empathy and antisocial traits (0.9 vs. 0.1, d = 1.18, 95% CI: [0.78–1.59]), and self-rated child sexual abuse risk (1.0 vs. 0.0, d = 1.56, 95% CI: [1.13–1.98]). When summarizing all five domains into a pre-specified composite score (0–15 points), PD subjects scored substantially higher than matched control men (7.5 vs. 2.1, d = 2.12, 95% CI: [1.65–2.59]). Five (9%) PD participants self-reported any previous conviction for a contact child sexual offense and eight (15%) for possession of child sexual abuse material or non-contact sexual offending (adult or child victim). Eighteen subjects (34%) acknowledged past week, child-related sexual behaviors. Conclusion Self-referred, help-seeking men with PD scored higher (small to very large effect sizes) than non-clinical control men on psychiatric measures of dynamic risk of child sexual abuse suggested in prior research with correctional samples diagnosed with PD. Our findings, including the composite risk measure, might inform clinical practice, but needs validation against actual sexual offending behavior.